Successful Source Identification and Control of an Outbreak of Serratia marcescens Bacteremia in NICU of a Tertiary Care Hospital in Eastern India - Aniruddha Ghosh; Kheya Ghosh Uttam; Rafiqul Hassan; Partha Pratim Halder; Sumon Poddar (Pediatric Review: International Journal of Pediatric Research, 2022)
Introduction: S. marcescens can cause potentially fatal sepsis, especially in premature and low birth weight babies. The result of an outbreak in any hospital is grave and requires thorough environmental sampling for source identification.Purpose: The objective of our study was to identify the source of the Serratia marcescens outbreak among the neonates admitted to the Neonatal Intensive Care Unit (NICU) of a tertiary care pediatric hospital. Seven neonates were affected in this outbreak and the index case, unfortunately, died.Materials &Methods: Apart from attempts to isolate organisms from neonates with sepsis, extensive environmental sampling in the form of swabs were collected from all surfaces like walls, floors, cradles, ventilators etc. and instruments like milk collecting devices, intravenous fluid and drug bottles etc. as well as from hands, stethoscopes, mobile phones of doctors and nursing staffs. Swabs were cultured to isolate S. marcescens, and a sensitivity pattern was noted.Results: Among the 78 samples studied, S. marcescens was isolated from a running intravenous fluid bottle and a normal saline bottle used for reconstituting intravenous fluids for the neonates. These isolates showed the same sensitivity patterns as those obtained from the affected neonates. Elimination of sources, appropriate antibiotic therapy and constant surveillance, achieved successful outbreak control.Conclusions: Extensive environmental sampling to find out the point source, and after that, active surveillance is necessary to control such infections. Besides source control and appropriate antibiotic therapy, implementing and reinforcing routine measures such as hand hygiene are compulsory in these outbreaks.